2014
DOI: 10.1088/0067-0049/215/1/11
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Dependence of Pulse Width for 150 Radio Normal Pulsars

Abstract: The frequency dependence of pulse width is studied for 150 normal pulsars, mostly selected from the European Pulsar Network, for which the multifrequency 10% pulse widths can be well fit with the Thorsett relationship W 10 = Aν µ + W 10,min . The relative fraction of pulse width change between 0.4 GHz and 4.85 GHz, η = (W 4.85 − W 0.4 )/W 0.4 , is calculated in terms of the best-fit relationship for each pulsar. It is found that 81 pulsars (54%) have η < −10% (group A), showing considerable profile narrowing a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 62 publications
6
47
1
Order By: Relevance
“…Mitra & Rankin 2002). Assuming a power law dependence of the frequency on widths, W ν ∝ ν a , we find, a ∼-0.19 ± 0.1, which agrees with previous results (Mitra & Deshpande 1999;Mitra & Rankin 2002;Chen & Wang 2014). There was one notable exception to the above results, PSR J1034-3224, where the ratio of widths was significantly larger than unity.…”
Section: Pulse Widthssupporting
confidence: 92%
“…Mitra & Rankin 2002). Assuming a power law dependence of the frequency on widths, W ν ∝ ν a , we find, a ∼-0.19 ± 0.1, which agrees with previous results (Mitra & Deshpande 1999;Mitra & Rankin 2002;Chen & Wang 2014). There was one notable exception to the above results, PSR J1034-3224, where the ratio of widths was significantly larger than unity.…”
Section: Pulse Widthssupporting
confidence: 92%
“…Thus, despite the low frequencies involved the interplay between GR and plasma effects in pulsars may potentially be within observable ranges (Popov et al 2006;Malov & Malofeev 2010;Stappers et al 2011). It is also significant to note the existence of a subset of radio pulsars with pulse widths that broaden with increasing frequency (Chen & Wang 2014), also seen in Figs. 4 and 5 for the toy light curves generated here.…”
Section: Discussionmentioning
confidence: 73%
“…Normal radio pulsars show a rich variety of frequencydependent behaviours (Chen & Wang 2014). A proportionality constant 10 3 < κ < 10 5 is needed to describe the dense environment surrounding these objects (Istomin 2001).…”
Section: Discussionmentioning
confidence: 99%
“…4.1). Chen & Wang (2014), who recently analysed the pulse width evolution with frequency of 150 pulsars from the EPN database, reached a similar conclusion: the emission must be broad-band, and the observed behaviour of width at different frequencies is caused by spectral changes along the flux tube. They found that if the spectral index variation along pulse phase is symmetric, there can be either canonical RFM or anti-RFM, while in cases where there are substantial deviations from the symmetric case, then there can be the non-monotonic trends of w 10 with ν, which we also observed.…”
Section: Some Examples Of Unexpected Profile Evolutionmentioning
confidence: 75%